Indigenous Tourism and the Barents Euro-Arctic Region (BEAR) - Olsen, Kjell Ole Kjærland (Arctic and North, 2019)
Source at http://www.arcticandnorth.ru/en/. In this article, it is argued that indigenous tourism must be understood as shaped by European ideas of the Other, as well as a more recent development in global politics. Such broad and increasingly global structures frame those heterogeneous populations that are labeled and label themselves indigenous. Furthermore, the current situation of these peoples is also shaped by their relationships to surrounding majorities and nation states. Therefore, definitions of indigenous tourism should rather be built on minorities’ degree of control of tourism activities than by ideas of emblematic cultural features. The growth in the tourism industry in many parts of the Barents Euro-Arctic Region also represents an opportunity for representing and maintaining cultural features among minorities. Nevertheless, minorities might also face challenges by being relegated to a position in the tourism industry where other more powerful actors define a rather narrow field of what indigenous tourism is. This article is based on literary studies of contemporary research on indigeneity, tourism, and Sámi tourism and draws upon the author’s extensive previous research on Sámi tourism in Norway.